1998
DOI: 10.1051/analusis:199826080057
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of starch origin and modifications by chemometrics spectral data processing (in French).

Abstract: L' a u t h e n t i fi c ation des aliments est une préoccupat i o n m a j e u re, tant pour le consommateur que pour l'ind u s t rie alimentaire et ce, à tous les niveaux de la chaîne de production : des mat i è res pre m i è res au pro d u i t fini. L'importance des amidons est reconnue depuis longtemps, car ils constituent une importante source d'énergie et contribuent à la structure et à la texture des aliments [1]. L'amidon peut être isolé à partir de différentes espèces végé-tales, des céréales comme le m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Having the disadvantages of these methods in mind, here we decided to use self-organizing maps (SOM). This algorithm has become a valuable tool for data analysis purposes [12][13][14][15][16][17][18][19][20][21][22]. The most commonly used SOM algorithm is for clustering multidimensional data [12][13][14][15][16][17][18][19] and for process/reaction monitoring [22,23], but also as a tool for variable selection [24].…”
Section: Introductionmentioning
confidence: 99%
“…Having the disadvantages of these methods in mind, here we decided to use self-organizing maps (SOM). This algorithm has become a valuable tool for data analysis purposes [12][13][14][15][16][17][18][19][20][21][22]. The most commonly used SOM algorithm is for clustering multidimensional data [12][13][14][15][16][17][18][19] and for process/reaction monitoring [22,23], but also as a tool for variable selection [24].…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, qualitative analysis (unsupervised approach) was reduced to principal component analysis or a classical cluster analysis (see Alonso-Salces et al, 2005;. To our knowledge, the first implementations of som on spectral data were due to Caceres-Alonso and Garcia-Tejedor (1995) and Vandeerstraeten et al (1998). In the last study, the authors showed how the Kohonen map enabled us to determine starch clusters based on their infrared spectra.…”
Section: Introductionmentioning
confidence: 99%